Implementation of the 2013 Curriculum Theory of John Dewey's Perspective Empire Philosophy for the Madrasah Ibtidaiyah Teacher - Dian Dian; Saepul Rizal; Yayang Khaeriah (STAI Hubbulwathan Duri, 2022)
This study was motivated by the fact that teachers had many difficulties adopting the 2013 curriculum, particularly the new 2013 curriculum set at a private Madrasah Ibtidaiyyah. The goal of this study was to determine teachers' grasp of the 2013 Curriculum in terms of planning, implementation, and assessment of the learning process. The study's subjects were seven teachers and it was done at the start of the 2021/2022 school year. This is a qualitative study using the descriptive method. Data is gathered using a variety of means, including questionnaires, observations, and documentation. The expert assessment was used to conduct the instrument validity test (Judgement Expert). According to the findings of the study, 1) teachers' understanding of the 2013 curriculum as seen from planning is in the category Often (61 percent -80 percent) and the percentage of understanding is 73 percent; 2) teachers' understanding of the 2013 curriculum as seen from implementation is in the Rare category (61 percent -80 percent) and the percentage of understanding is 65 percent; and 3) teachers' understanding of the 2013 curriculum as seen from implementation is in the Rare category (61 percent -80 percent) and the percentage of understanding is 70 percent